Alder creek sanidine (ACs-a): New sampling and intercalibration for quaternary 40Ar/39Ar age monitoring. (May 2023) - Wang, Yinzhi; Wang, Fei; Shi, Wenbei; Yang, Liekun; Wu, Lin
Abstract: The 40 Ar/ 39 Ar dating method requires the utilization of a neutron flux monitoring reference material. Generally, the extracted sanidine from the rhyolite of Alder Creek, California, is regarded as a reliable indicator for Quaternary materials; however, its availability in many laboratories is still limited. A new sampling method of Alder Creek rhyolite, which could yield pure and fresh sanidine crystals designated as Alder Creek sanidine (ACs-a), could be used to produce a new batch of the reference material. Accordingly, in this work, the grains of sanidine were meticulously dated and calibrated against the international reference materials FCs, YBCs, and ACs-2. Additionally, at various grain sizes (>1000 μm and 1000–600 μm), the degree of homogeneity of the newly selected grains was evaluated and confirmed. Experiments involving total laser fusion and incremental heating were also conducted to compare the outcomes of the different applied protocols. In situ trace elemental analysis by electron microprobe analysis (EMPA) revealed the existence of consistent K content. Flat age spectra and average F-value ( 40 Ar*/ 39 ArK ) relative standard deviations ranging from 0.36% to 0.51% for the different aliquots reveal the reproducibility of ACs-a and its appropriateness as a reliable 40 Ar/ 39 Ar standard. The calibrated age of ACs-a was 1.1888 ± 0.0048 Ma (0.40%, MSWD = 1.9) and the intercalibration factors (R-values) between ACs-a and FCs, YBCs, and ACs-2 were R F C s A − 1 = 0.04184 ± 0.00030, R F C s A − 4 = 0.04178 ± 0.00018, R Y B C s A − 2 = 0.04005 ± 0.00041, R Y B C s A − 5 = 0.03998 ± 0.00019, and R A C s − 2 A − 3 = 0.99271 ± 0.01148. These R-values enabled direct comparisons between ACs-a and other reference materials. The ACs-a grains are available from our laboratory upon request as a neutron fluence monitor. Highlights: We are reporting a new batch of the ACs standard: ACs-a sanidine. ACs-a shows good single-crystal reproducibility on K content, F value and age. ACs-a is freely available to the 40 Ar/ 39 Ar community.